(untitled) (New York, 2010)
A comprehensive and timely reference of pediatric neurological problems for practitioners on the go. Particularly given the uneasiness many non-neurologists feel in dealing with these issues, this book can be a genuine help....this book is a very useful initial reference for general pediatric practitioners, adult neurologists, and neurology trainees. The many tables, illustrations, and pictures are a particular strength. It certainly is worthy of consideration as a reference for one's bookshelf.
Keywords: Nervous System Diseases,Hệ thống bệnh thần kinh; Diagnosis,Chẩn đoán